Implementation of Religious Character Education at State Islamic Elementary School 2 Bengkulu City - Fhinda Alphadila; Diva Selfi. N; Azizah Aryati; Fera Zasrianifa; Dalima Septiria (International Journal on Advanced Science, Education, and Religion, 2025)
The abstract is written in one paragraph containing at least the objectives, methods, and results of the study. This study aims to describe the implementation of religious character education at Madrasah Ibtidaiyah Negeri 2 Bengkulu City and the factors that influence it. This study uses a qualitative approach with descriptive methods. The research subjects consisted of the madrasah principal, teachers, and students who were selected purposively based on their involvement in religious activities. Data collection techniques were carried out through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The validity of the data was tested using triangulation of sources and techniques. The results of the study indicate that religious character education is implemented through various habituation activities such as dhuha prayer, congregational prayer, reciting prayers before and after studying, as well as the habituation of discipline and politeness in the madrasah environment. Teachers play an important role as role models in the formation of students' religious character, supported by a religious madrasah environment. However, several obstacles were still found, such as a lack of student discipline, a lack of respect for teachers, and inconsistent implementation of the habituation. This shows that the implementation of religious character education has been running but is not yet optimal and still requires strengthening cooperation between teachers, parents, and the environment..